Education In Motion. Employing modular classrooms to create vibrant, collaborative, and flexible learning environments in the Seattle School District. - Schaat, Rauland Dallas (My University, 2017)
The Seattle Public School District (SPS) has been experiencing an increase of 1000 students per year for the past five years. In the Seattle Public School District a common solution to alleviate the issues capacity overruns and budgetary constraints is to install modular classrooms. These spaces are effective in delivering almost immediate, economical learning space. However, where this building typology falls short is in its indoor environmental quality, durability, and spatial relationships. This doesn’t need to be the case. With a greater emphasis placed on the design of modular classrooms as educational space, a re-tooling of the fabrication process, the use of digital fabrication technologies, and the advent of the new structural technology of engineered heavy timber, modular classrooms are uniquely positioned to bridge the gap between cheap temporary modular classroom space and expensive highly customized permanent classroom space. Altering the design, fabrication, and assembly processes for modular classrooms gives this typology the capability to create vibrant, collaborative, semi-permanent educational space to schools while also allowing a level of future flexibility to school districts.
Thesis (Master's)--University of Washington, 2016-12
Keywords: classroom; digital-fabrication; modular; pre-fabrication; schools; seattle; Architecture; architecture